2012
DOI: 10.1038/aps.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin enhances neurite outgrowth in cortical neurons in vitro via up-regulating the Akt/mTOR and Akt/GSK-3β signaling pathways

Abstract: Aim: To investigate whether atorvastatin can promote formation of neurites in cultured cortical neurons and the signaling mechanisms responsible for this effect. Methods: Cultured rat cerebral cortical neurons were incubated with atorvastatin (0.05-10 μmol/L) for various lengths of time. For pharmacological experiments, inhibitors were added 30 min prior to addition of atorvastatin. Control cultures received a similar amount of DMSO. Following the treatment period, phase-contrast digital images were taken. Dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 55 publications
2
43
1
Order By: Relevance
“…Primary cultures were obtained from the hippocampi of 0-to 24-h-old Sprague-Dawley rats as previously described [31] . The cultures were plated on poly-L-lysine-coated 16-mm-diameter coverslips (~150 cells/mm 2 ) for immunocytochemistry assays or 6-well culture plates (1×10 6 ) for Western blot analysis.…”
Section: Primary Hippocampal Neuron Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cultures were obtained from the hippocampi of 0-to 24-h-old Sprague-Dawley rats as previously described [31] . The cultures were plated on poly-L-lysine-coated 16-mm-diameter coverslips (~150 cells/mm 2 ) for immunocytochemistry assays or 6-well culture plates (1×10 6 ) for Western blot analysis.…”
Section: Primary Hippocampal Neuron Culturesmentioning
confidence: 99%
“…Western blot analysis were performed for the detection of synaptophysin, PSD-95, and p38MAPK, as previously described [31] . Fresh hippocampal tissue or cultured hippo-www.chinaphar.com Zhang LL et al Acta Pharmacologica Sinica npg campal neurons were lysed in RIPA buffer.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In our study, we found that atorvastatin pretreatment prevented AβO-induced decreases in Ser-9 phosphorylation in hippocampal neurons, suggesting decreased activity of GSK3β. Additionally, our previous study demonstrated that atorvastatin enhanced neuronal neurite outgrowth through up-regulation of the Akt/GSK3β signaling pathway [21] .…”
Section: Discussionmentioning
confidence: 93%
“…Hippocampal cultures were prepared from embryonic Sprague-Dawley rats as previously described [21] . The hippocampi of E18/19 rat fetuses were collected in Hanks' solution without Ca 2+ and Mg 2+ (D-Hanks).…”
Section: Primary Hippocampal Neuron Culturesmentioning
confidence: 99%
“…Transcription factors are essential for the initiation of target gene transcription for the further production of transcription factors or the translation of other genes that play roles in the retraction, regrowth, and reorganization of dendritic branches [4][5][6]. Much of what we know about the roles transcription factors play in these processes stem from limited studies on the actions of a handful of key factors.…”
Section: Introductionmentioning
confidence: 99%